Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Prove identity tan 3x−tan 2x−tanx = tan 3xtan 2xtanx

Sagot :

tan ( a + b ) = [ tan a + tan b ] / [ 1 - (tan a)*(tan b) ];

let be a = 2x and b = x;

=> tan 3x = [ tan 2x + tan x ] / [ 1 - (tan 2x)*(tan x) ] => (tan 3x)*[ 1 - (tan 2x)*(tan x) ] =
 
tan 2x + tan x => tan3x -  tan 3xtan 2xtanx = tan 2x + tan x =>  tan 3x−tan 2x−tanx = tan 3xtan 2xtanx.